Analysis of Intelligence and National Security in Latin America: Bibliometric Analysis - Pimentel Bernal, Marcelo; Veliz, Jose Carlos; Lazo, Liliana (Compendium: Cuadernos de Economía y Administración; Vol. 11 Núm. 1 (2024): Revista Compendium: Cuadernos de Economía y Administración, 2024)
Intelligence analysis (IA) consists of the collection, processing and analysis of classified information with the objective of identifying and preventing national security (NS) threats. NS encompasses a wide range of concerns related to sovereignty, homeland defense, and prevention of internal and external threats. While the use of IA in NS is valuable, it may have limitations by focusing on specific aspects and restricting addressing broader needs to ensure NS. This reveals a gap in the comprehensive understanding of the challenges and threats to a country, as the specific focus of IA does not encompass the broad vision needed in the NS. In this regard, bibliometric research was developed in which 416 articles from the Scopus and WOS database were analyzed using the WOSviewer and Biblioshiny tools. It was found that among the most cited authors were Schultze Ulrike and Choo Kim-Knag. In addition, among the most cited sources were the journal Information Visualization and Intelligence and National Security. Also, among the most frequently used keywords were "Intelligent Analysis" and "Artificial Intelligence". It was concluded that the study of AI is in development, the concern of which integrates artificial intelligence and cyber-attack threats